Inguinal lymph node metastasis of colon cancer - Sloane McGraw; Jigisha Thakkar; Divyesh Mehta (Indian Journal of Medical and Paediatric Oncology)
We present a case of adenocarcinoma of colon with unusual metastasis to inguinal lymph nodes. Our patient is a young male with bilateral inguinal lymphadenopathy, bone pains, and jaundice who presented as carcinoma of unknown primary. He was diagnosed as widely metastatic adenocarcinoma of colon for which he received chemotherapy and has had a good response to the treatment.